Key Factors in Fashion Purchase Decisions on Social Media - Nurhasan, Rohimat; Munawi, Ahmad Syarif; Wufron, Wufron; Muminin, Riyad Sabilul (Fakultas Ekonomi Universitas Garut, 2024)
TikTok is an application that provides entertainment content that is in great demand. Over time, the use of TikTok has changed; it was originally only used as an entertainment venue, and now TikTok is also used as a business medium. Therefore, various business activities are increasingly found on this social media platform. This research aims to determine the factors that drive decisions to purchase fashion products on TikTok social media, as well as to identify the most dominant factors in driving decisions to purchase fashion products on this platform. The research methods used are descriptive analysis and exploratory factor analysis. The data collection technique was carried out through distributing questionnaires. The sampling used in this research was nonprobability sampling with a total of 100 respondents. The analysis technique used is factor analysis with the help of the SPSS analysis tool. Based on the research results, it was found that the factors that drive decisions to purchase fashion products on TikTok social media include interest, need, price, product, and trust. Apart from that, the most dominant factor in driving decisions to purchase fashion products on TikTok social media is interest, which has the highest eigenvalue compared to other factors.